PERANAN PEMERINTAH DALAM PENANGANAN KONFLIK SOSIAL PADA KELURAHAN KENANGAN KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Lawolo, Lestari; Sinaga, Rudi Salam; Lubis, Khairunnisah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Goal achieved from this research is to find government handling social conflict in Kenangan Village, Percut Sei Tuan District, Deli Serdang Regency. How efforts government's handling social conflict in Kenangan Village, Percut Sei Tuan District, Deli Serdang Regency. Research method is a qualitative method descriptive approach. Results research Lurah Handling Social Conflict Kenangan Village, Percut Sei Tuan District, Deli Serdang Regency quite good, Lurah providing various education and understanding community about ethnic, cultural and religious diversity. Addition, lurah also gave information community about cultivating tolerance, cooperation, mutual cooperation, mutual respect and respect among fellow ethnicities, religions and nations. Furthermore, Lurah was cooperate with the police, TNI, and community leaders solving sara issue, especially in Kenangan Village, Percut Sei Tuan District, Deli Serdang Regency.